2014
DOI: 10.1002/0471142727.mb0716s106
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Fitness and Genetic Interactions Determined by Tn‐seq, a High‐Throughput Massively Parallel Sequencing Method for Microorganisms

Abstract: The lagging annotation of bacterial genomes and the inherent genetic complexity of many phenotypes is hindering the discovery of new drug targets and the development of new antimicrobials and vaccines. Here we present the method Tn-seq, with which it has become possible to quantitatively determine fitness for most genes in a microorganism and to screen for quantitative genetic interactions on a genome-wide scale and in a high-throughput fashion. Tn-seq can thus direct studies in the annotation of genes and unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 44 publications
(58 reference statements)
0
57
0
Order By: Relevance
“…S1AB ) . The presence of Mme I sites allows for digestion of genomic DNA containing Krmit transposon insertion sites (TIS), producing uniform 20-nt regions of adjacent chromosomal DNA (insertion tags) for next-generation sequencing and Tn-seq screens 31 . Initial tests for in vivo transposition using pKRMIT in a GAS serotype M1T1 strain revealed that Krmit transposed comparably to Oskar 28 29 , exhibiting an average transposition frequency of 4 × 10 −3 with insertions occurring exclusively within the dinucleotide TA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1AB ) . The presence of Mme I sites allows for digestion of genomic DNA containing Krmit transposon insertion sites (TIS), producing uniform 20-nt regions of adjacent chromosomal DNA (insertion tags) for next-generation sequencing and Tn-seq screens 31 . Initial tests for in vivo transposition using pKRMIT in a GAS serotype M1T1 strain revealed that Krmit transposed comparably to Oskar 28 29 , exhibiting an average transposition frequency of 4 × 10 −3 with insertions occurring exclusively within the dinucleotide TA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The complexity of the Krmit mutant libraries in M1T1 5448 was examined by Tn-seq 26 31 with modifications for its use in GAS with Krmit . Briefly, genomic DNA was isolated from the different mutant pools (T 0 to T 3 ), subjected to complete digestion by Mme I followed by ligation to Mme I adapters, and PCR amplification to produce DNA-seq libraries consisting of 176-bp Krmit -specific insertion tags containing adjacent genomic sequence, Illumina-specific sequences and one of 8 distinct barcodes for multiplexing.…”
Section: Resultsmentioning
confidence: 99%
“…Given the global changes effected by RpoS in stationary phase (24), we wished to know which RpoS-regulated genes protected cells from SDS in stationary phase. In order to address this question, we utilized a transposon mutant pool sequencing (Tn-Seq) experiment (46). We created a pooled library of approximately 190,000 mutants, each containing an EZ-Tn5 insertion, grew this library overnight to stationary phase under either nitrogen-limiting or carbon-limiting conditions, and collected genomic DNA samples from these cultures before and after 24 h of 2% SDS treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tn mutant libraries were characterized by Tn-seq, essentially as described previously (28, 29). Briefly, genomic DNA from Tn mutant libraries was isolated using the DNeasy blood and tissue kit (Qiagen) but, before the manufacturer's recommendations for Gram-negative bacteria were followed, cells were washed once with 1 M NaCl and once with PBS.…”
Section: Methodsmentioning
confidence: 99%